Lithuanian Synagogues: From the First Descriptions to Systematic Research - Vilma Gradinskaite (Arts, 2020)
The article presents an analysis of the development stages of synagogue research methodology in Lithuania during the four major historical periods of the country—Lithuania in the Russian Empire (1795–1918), Vilnius Region in the interwar period and the independent Republic of Lithuania (1918–1940), the Soviet period (1940–1990), and the independent Republic of Lithuania restored in 1990. Each chapter of the article deals with the issues of synagogue research, heritage conservation and management, while the part about the restored independent Republic of Lithuania and modern days includes topical issues related to synagogue restoration, commemoration and putting them into operation. The study uses two different sources: archival materials and publications. Written sources and publications are reviewed in chronological order and start from the end of the 18th century. The study employs several research methods—the historical descriptive method, the comparative method and the analysis method.